Entre el estilo y el método: el estatuto de la narrativa en la comprensión de los universos psico-socio-culturales (2005)
The article discusses the narrative like a propitious genre to promote understandings that integrate the psychological, social and cultural universes. The first part identifies the statute of the narrative in the epistemological and methodological conflicts of human and social sciences. The second part locates the narrative within the possibilities of clinical psychology, specifically from the systemic approach. Index terms: psychologic theory, narrative, method, systemic focus, clinical psychology.